Comparative Transcriptomics Among Four White Pine Species. Issue 5 (1st May 2018) - Baker, Ethan A G; Wegrzyn, Jill L; Sezen, Uzay U; Falk, Taylor; Maloney, Patricia E; Vogler, Detlev R; Delfino-Mix, Annette; Jensen, Camille; Mitton, Jeffry; Wright, Jessica; Knaus, Brian; Rai, Hardeep; et al.
Abstract: Conifers are the dominant plant species throughout the high latitude boreal forests as well as some lower latitude temperate forests of North America, Europe, and Asia. As such, they play an integral economic and ecological role across much of the world. This study focused on the characterization of needle transcriptomes from four ecologically important and understudied North American white pines within the Pinus subgenus Strobus . The populations of many Strobus species are challenged by native and introduced pathogens, native insects, and abiotic factors. RNA from the needles of western white pine ( Pinus monticola ), limber pine ( Pinus flexilis ), whitebark pine ( Pinus albicaulis), and sugar pine ( Pinus lambertiana ) was sampled, Illumina short read sequenced, and de novo assembled. The assembled transcripts and their subsequent structural and functional annotations were processed through custom pipelines to contend with the challenges of non-model organism transcriptome validation. Orthologous gene family analysis of over 58, 000 translated transcripts, implemented through Tribe-MCL, estimated the shared and unique gene space among the four species. This revealed 2025 conserved gene families, of which 408 were aligned to estimate levels of divergence and reveal patterns of selection. Specific candidate genes previously associated with drought tolerance and white pine blister rust resistance in conifers were investigated.